2016
DOI: 10.1128/iai.01168-15
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Peroxiredoxin 6 by the Pla Protease of Yersinia pestis

Abstract: Pneumonic plague represents the most severe form of disease caused by Yersinia pestis due to its ease of transmission, rapid progression, and high mortality rate. The Y. pestis outer membrane Pla protease is essential for the development of pneumonic plague; however, the complete repertoire of substrates cleaved by Pla in the lungs is not known. In this study, we describe a proteomic screen to identify host proteins contained within the bronchoalveolar lavage fluid of mice that are cleaved and/or processed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…A). Therefore, to assess the impact of Pla on PAI‐1 levels when bacterial loads were equivalent, we increased the inoculum (‘input CFU’) of Y. pestis ∆ pla to 10 8 , so that the output CFU at 48 h was matched to the output CFU of the wild‐type strain . We found no difference in the levels of total PAI‐1 in the lungs at 48 h when output CFUs were equivalent (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…A). Therefore, to assess the impact of Pla on PAI‐1 levels when bacterial loads were equivalent, we increased the inoculum (‘input CFU’) of Y. pestis ∆ pla to 10 8 , so that the output CFU at 48 h was matched to the output CFU of the wild‐type strain . We found no difference in the levels of total PAI‐1 in the lungs at 48 h when output CFUs were equivalent (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Mice were inoculated intranasally with Y. pestis , and at 48 h mice were killed and the lungs were inflated with 1 mL of 10% neutral buffered formalin via tracheal cannulation, removed, fixed in 10% formalin, embedded in paraffin, and stained with hematoxylin and eosin, as previously described . Inflamed lesions were analyzed with imagej to calculate the area of inflammation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it was shown that Pla provides proteolytic processing of the Y . pestis autotransporters YapG and YapE [24, 25], cleaves and inactivates mammalian thrombin-activatable fibrinolysis inhibitor (TAFI) [26], plasminogen activator inhibitor 1 (PAI-1) [27, 28], endogenous anticoagulant tissue factor pathway inhibitor (TFPI) [29], host factor peroxiredoxin 6 [30], and degrades the apoptotic signaling molecule Fas ligand (FasL) [31]. Finally, murine C-type lectin receptor DEC-205 (CD205) expressed on both alveolar macrophages and pulmonary dendritic cells is a receptor for Pla of Y .…”
Section: Introductionmentioning
confidence: 99%